Chimeric antigen receptor-modified T cells for the treatment of solid tumors: Defining the challenges and next steps() - Beatty, Gregory L. (Pharmacol Ther, 2016)
Chimeric antigen receptor (CAR) T cell therapy has shown promise in CD19 expressing hematologic malignancies, but how to translate this success to solid malignancies remains elusive. Effective translation of CAR T cells to solid tumors will require an understanding of potential therapeutic barriers, including factors that regulate CAR T cells expansion, persistence, trafficking, and fate within tumors. Herein, we describe the current state of CAR T cells in solid tumors; define key barriers to CAR T cell efficacy and mechanisms underlying these barriers, outline potential avenues for overcoming these therapeutic obstacles, and discuss the future of translating CAR T cells for the treatment of patients with solid malignancies.